Fetomaternal outcomes in premature rupture of membranes at term: a case control study - Shetty, Suprajna; Shetty, Harish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Premature rupture of membranes is defined as spontaneous rupture of fetal membranes beyond 28weeks of pregnancy but before the onset of uterine contractions. It occurs in approximately 10% of all pregnancies and in 70% it occurs at term. If PROM occurs before 37 completed weeks, it is referred as preterm premature rupture of membranes(PPROM). PROM is associated with adverse outcomes in both, hence its management becomes crucial. It complicates 8% of pregnancies. Objective of present study was to investigate the labour, maternal and perinatal outcomes. Methods: 75 patients who entered labour room at term with PROM were taken as cases and those with intact membranes as controls. Investigations are sent, and prophylactic antibiotics were given. Progress of labour, PROM delivery interval, method of induction, mode of delivery along with maternal and fetal outcomes, total duration of hospital stay was noted and compared with controls. Results: Rate of caesarean is higher in study group (14.7%) and failure to progress was the common indication. Intrapartum morbidity was higher in the study group (16%) and perinatal morbidity was 20%. NICU admission and the need for antibiotics were higher in study group and hence longer duration of hospital stay. Conclusions: PROM is associated with increased incidence of neonatal sepsis and subsequently antibiotics given were higher in cases. There is a higher incidence of caesarean rates and hospital stay. Proper screening of high risk cases and appropriate management is suggested to reduce perinatal morbidity.